When (Non)Differences Make a Difference: The Roles of Demographic Diversity and Ideological Homogeneity in Overcoming Ideologically Biased Decision Making - Solomon, Brittany C.; Hall, Matthew E. K. (Organization Science, 2023)
Increasing demographic diversity is undoubtedly important and can aid in debiasing decision makers. Yet, the promises of demographic diversity are not always realized due to social integration problems. We consider why and for whom differences combined with homogeneity make a difference for groups in terms of integratively complex thinking and ideological decision making. Although research has shown that decision makers often rely on political biases, that work has not addressed when and why decision-making groups are able to overcome these biases—a pervasive concern in today’s politically polarized social milieu. Drawing on the common in-group identity model and research on integrative complexity, we theorize that demographic diversity ultimately yields less ideological decision making because it prompts integrative complexity; however, demographic diversity only accrues this benefit in the presence of ideological homogeneity. We also reason that the relationship between integrative complexity and reduced ideological decision making emerges for more conservative (versus more liberal) groups. We find support for our expectations using a natural experiment of judges on the U.S. Courts of Appeals. Supplemental analyses indicate that working within a demographically diverse and ideologically homogeneous group also positively predicts integrative complexity in future decision-making groups. Finally, we find that demographic and ideological diversity can substitute for one another, but no additional integrative complexity benefits accrue when both are present. We discuss implications of this research in light of the ongoing conversation about the value of diversity and today’s polarized political climate. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.1647 .